2009
DOI: 10.1002/tie.20256
|View full text |Cite
|
Sign up to set email alerts
|

Formal institutions and foreign direct investment

Abstract: This study examines the impact of formal institutions on foreign direct investment. First, the quality (strength or weakness) of formal institutions in host countries is analyzed. Second, the absolute differences in the quality of formal institutions between the host and home countries are examined. The results show that (1) strong formal institutions in host countries positively influence FDI flows and (2) the larger the institutional distance between the home and host country, the lesser the FDI inflows. © 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…By examining the effects of the World Bank's notion of good governance on FDI inflows in 15 Asian countries, Mengistua and Adhikary () find that political stability and absence of violence, government effectiveness, rule of law, and control of corruption are the key determinants of FDI inflows. These findings highlight the importance of improving the domestic governance environment for attracting FDI inflows, which is also confirmed by Seyoum (), finding that strong formal institutions in host countries attract more FDI flows. Hsu and Tiao () investigate the relationship between patent rights protection and inward FDI in 11 Asian countries, and their empirical results indicate that the strengthening of patent rights protection has a positive impact on inward FDI in Asian countries.…”
Section: Theoretical Background and Model Developmentsupporting
confidence: 75%
See 1 more Smart Citation
“…By examining the effects of the World Bank's notion of good governance on FDI inflows in 15 Asian countries, Mengistua and Adhikary () find that political stability and absence of violence, government effectiveness, rule of law, and control of corruption are the key determinants of FDI inflows. These findings highlight the importance of improving the domestic governance environment for attracting FDI inflows, which is also confirmed by Seyoum (), finding that strong formal institutions in host countries attract more FDI flows. Hsu and Tiao () investigate the relationship between patent rights protection and inward FDI in 11 Asian countries, and their empirical results indicate that the strengthening of patent rights protection has a positive impact on inward FDI in Asian countries.…”
Section: Theoretical Background and Model Developmentsupporting
confidence: 75%
“…In the international business literature, recent empirical evidence has shown that effective institutional environment in a host country is an important determinant of foreign direct investment inflows (Globerman & Shapiro, ; Hsu & Tiao, ; Mengistua & Adhikary, ; Seyoum, ). Using international data on FDI inflows and outflows, Globerman and Shapiro () find that good governance affects the security of property rights and transparency of government and legal processes, and thus attracts more FDI inflows.…”
Section: Theoretical Background and Model Developmentmentioning
confidence: 99%
“…Oh and Rugman () found that 60% of the largest European firms used a regional integration strategy with only 5% using a global production strategy. Similarly, Seyoum () found that countries with strong institutions (such as DCs) tend to invest in other countries with strong institutions.…”
Section: Introductionmentioning
confidence: 95%
“…Market-supporting institutions are important because they are a fundamental cause of long-term growth in a country (Acemoglu, Johnson, and Robinson, 2005;Rodrick, 2000): they ensure that property rights are respected and protected, promises are trusted and enforced, that competition is fostered, and that information flows smoothly (McMillan, 2007;Peng, 2002;Tan, 2002). As noted above, development of market-supporting institutions is a major characteristic of EMs (Hoskisson et aI., 2000;Wright et aI., 2005) and continually fuels rapid economic growth in these markets (Beck and Levine, 2005;Dunning and Lundan, 2008;Globerman and Shapiro, 2003;Llewellyn, 1925;Seyoum, 2009). Tan (2002), for example, conducted a quasi-experimental design to isolate the role of cultural and national differences among mainland Chinese, Chinese Americans, and…”
Section: Market-supporting Institutional Development and Sub-nanonalvmentioning
confidence: 99%